Alzheimer disease: evidence for susceptibility loci on chromosomes 6 and 14. - Weitkamp, L R (1983)
We report the transmission of HLA haplotypes and Gm allotypes in 97 members of a single kindred containing 257 individuals, 45 of whom were determined by clinical examination, autopsy, or historical data to have had Alzheimer disease (AD). Extensive inbreeding suggests that more than one gene may contribute to susceptibility to AD in this family, despite the apparent vertical transmission of illness. The distribution of HLA haplotypes and of Gm allotypes to affected and unaffected siblings is consistent with the possibility that genes in the HLA region of chromosome 6 and perhaps also in the Gm region of chromosome 14 are determinants of susceptibility. Further studies are needed to investigate whether susceptibility to AD may result from an interaction between (immune response?) genes on these two chromosomes.